Pharmacokinetic and Pharmacogenetic Factors Contributing to Platelet Function Recovery After Single Dose of Ticagrelor in Healthy Subjects - Zhu, Qian; Zhong, Wanping; Wang, Xipei; Mai, Liping; He, Guodong; Chen, Jiyan; Tang, Lan; Liu, Shuwen; Lai, Weihua; Zhong, Shilong (Frontiers in Pharmacology, 2019)
Abstract Objectives This study aimed to elucidate the contribution of candidate single nucleotide polymorphisms (SNPs) related to pharmacokinetics on the recovery of platelet function after single dose of ticagrelor was orally administered to healthy Chinese subjects. Methods The pharmacokinetic profiles of ticagrelor and its metabolite AR-C124910XX (M8), and the platelet aggregation (PA), were assessed after 180 mg of single-dose ticagrelor was orally administered to 51 healthy Chinese subjects. Effects of CYP2C19*2, CYP2C19*3, CYP3A5*3, UGT1A1*6, UGT1A1*28, UGT2B7*2, UGT2B7*3, SLCO1B1 388A>G and SLCO1B1 521T>C, on the pharmacokinetics of ticagrelor and M8, and platelet function recovery were investigated. Results The time to recover 50% of the maximum drug effect (RT50) ranging from 36 h to 126 h with 46.9% CV had a remarkable individual difference and was positively associated with the half-life (t1/2) of M8 (r = 0.3901, P = 0.0067). The time of peak concentration (Tmax) of ticagrelor for CYP2C19*3 GG homozygotes was significantly higher than that of GA heterozygotes (P = 0.0027, FDR = 0.0243). Decreased peak concentration (Cmax) of M8 was significantly associated with SLCO1B1 388A>G A allele (P = 0.0152, FDR = 0.1368). CYP2C19*2 A was significantly related to decreased Cmax of M8 (P = 0.0455, FDR = 0.2048). While, the influence of these nine SNPs on the recovery of platelet function was not significant. Conclusion Our study suggests that the elimination of M8 is an important factor in determining the recovery of platelet function. Although CYP2C19 and SLCO1B1 genetic variants were related to the pharmacokinetics of ticagrelor and M8, they did not show a significant effect on the platelet function recovery in this study. Clinical Trial Registration https://clinicaltrials.gov/ct2/show/NCT03092076 (NCT03092076).